2023
DOI: 10.3390/plants12122317
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effect of Cooked Chickpea on Colon Carcinogenesis Evolution in AOM/DSS-Induced Balb/c Mice

Abstract: Chickpeas are one of the most widely consumed legumes worldwide and they might prevent diseases such as cancer. Therefore, this study evaluates the chemopreventive effect of chickpea (Cicer arietinum L.) on the evolution of colon carcinogenesis induced with azoxymethane (AOM) and dextran sodium sulfate (DSS) in a mice model at 1, 7, and 14 weeks after induction. Accordingly, the expression of biomarkers—such as argyrophilic nucleolar organizing regions (AgNOR), cell proliferation nuclear antigen (PCNA), β-cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Similar results were observed for the reduction in tumor size, with the dose of 3.0 mg/Kg being more effective than cisplatin. Other works report that mice administered AOM/DSS show colon shortening, changes in morphology, and tissue stiffness [47,56,57], agreeing with our results since the groups with induced CRC showed a decrease in colon length compared with the group of healthy mice. The histopathology results obtained by hematoxylin-eosin staining suggest that those mice administered LH displayed restoration of the damaged mucosa layer, recovery of the lamina propria, and the absence of adenoma and intramucosal carcinoma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were observed for the reduction in tumor size, with the dose of 3.0 mg/Kg being more effective than cisplatin. Other works report that mice administered AOM/DSS show colon shortening, changes in morphology, and tissue stiffness [47,56,57], agreeing with our results since the groups with induced CRC showed a decrease in colon length compared with the group of healthy mice. The histopathology results obtained by hematoxylin-eosin staining suggest that those mice administered LH displayed restoration of the damaged mucosa layer, recovery of the lamina propria, and the absence of adenoma and intramucosal carcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…Malnutrition is a common problem in CRC patients due to intestinal obstruction and cachexia [43] and has been associated with overexpression of cytokines such as interleukin-6 and tumor necrosis factor-alpha (TNF-α), as well as hormones that induce lack of appetite, and it has direct catabolic effects on skeletal muscle [44][45][46]. In a recent study, weight loss of more than 20% was observed in a colon cancer model induced with AOM/DSS [47], which is consistent with our results since the PC group presented a 31% decrease compared with the negative control. In addition to weight loss in animals, this model has been associated with other symptoms, such as severe colitis, diarrhea with bleeding, and the development of tumors in the colon [48].…”
Section: Discussionmentioning
confidence: 99%